Accuracy of the Identification and Prognosis Prediction of SOFA-Based Sepsis-3 for Septic Patients in the Emergency Department Compared With Sepsis-2 - Yi-Jie Zhang; Wei Fang; Zhen Wang (Emergency Medicine International)
Conclusion: Compared with Sepsis-2, Sepsis-3 identified more patients with sepsis and was suitable for ED use. The SOFA score had lower mortality prediction accuracy than the qSOFA score and NEWS, which could be significantly improved by combining with two/three variables (T, RR, and SBP).